(untitled) - Cosmo, Nicola Di (Cambridge, 2004)
The book explores the tensions existing between these two worlds as they became progressively more polarized, with the eventual creation of the nomadic Hsiung-nu empire in the north, and of the Chinese empire in the south. It is the first study that investigates the origins of the antagonism between early China and its "barbarian" neighbors combining both textual and archaeological data.
Keywords: Lịch sử,Lịch sử; Trung Quốc,Đông Á